(untitled) (Journal of Pathology of Nepal, 2012)
Background: Pancytopenia refers to a reduction in all the three cellular elements of blood. The aim of this study was to identify the various causes of pancytopenia in patients attending to Manipal teaching hospital in Pokhara. Materials and Methods: This was a cross-sectional study, carried out in Manipal teaching hospital from August 2008 to August 2010. Fifty-four patients with pancytopenia were included in the study. Complete blood count, bone marrow aspirations and trephine biopsies were performed. Data were analyzed using SPSS 11.0 version. Results: Out of 54 cases, there were 16 cases (29.60%) of hypoplastic bone marrow, 15 cases (27.78%) of hematological malignancies, 13 cases (24.10%) of megaloblastic anemia, 4 cases (11.11%) of erythroid hyperplasia and 6 cases (7.41%) of normcellular bone marrow. Acute myeloid leukemia was the commonest hematological malignancy. Conclusion: The commonest cause of pancytopenia in our study was hypoplastic bone marrow followed by hematological malignancies and megaloblastic anemia. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6023 JPN 2012; 2(3): 207-210